Critical Thinking Ability of High School Students in Daily Life Acid-base Concept - Das Salirawati; Erfan Priyambodo; Anggiyani R.E. Nugraheni; Rahmat Basuki (Pendidikan Kimia Unimus, 2021)
This study aimed to comprehend the quality of critical thinking questions and measure the critical thinking ability in the daily life acid-base topic of 2nd -students from six public high schools, six private high schools, and combination of them in Yogyakarta at the 2018/2019 academic year based on the answer patterns of students to the developed critical thinking questions. The method was an ex-post facto research designed with a one-sample design. The level of critical thinking ability was measured by 15 critical thinking question outlined from the seven critical thinking criteria referred to established commercial critical thinking test. The questions were theoretically validated by three reviewers (content, evaluation, and chemistry education experts). The results showed that the quality of critical thinking questions were excellent. The level of critical thinking skills in daily life acid-base topic of 2nd-grade Yogyakarta’s senior high schools at the academic year 2018/2019 of six public high schools, six private high schools, and combination both of them was 40.2% (moderate), 34.8% (deficient), 37.5% (deficient), respectively.